Serum Stem Cell Growth Factor Beta for the Prediction of Therapy Response in Hepatocellular Carcinoma - Sukowati, Caecilia H. C. (Biomed Res Int, 2018)
INTRODUCTION: Chronic inflammatory response is one of major contributors in the development of hepatocellular carcinoma (HCC). Inflammatory molecules, such as cytokines and growth factors in the circulation, can be useful in the diagnosis and prognosis of the patients. The stem cell growth factor beta (SCGFβ), a newly found protein, is a secreted sulfated glycoprotein and it functions as a growth factor for primitive hematopoietic progenitor cells. The level of SCGFβ had been reported to be elevated in several cancer types. However, there is very few or even no information on this protein in the study of HCC, even more in clinical studies. METHODS: A multiplex immunoassay panel of 48 cytokines and growth factors were utilized to screen 68 sera from 29 HCC patients at pretreatment (T0), 1 month (T1), and 6 months (T6) after treatment by either radiofrequency ablation (RF) or transarterial chemoembolization (TACE). Treatment response was evaluated according to mRECIST criteria. RESULTS: Immunoassay screening showed that the levels of IL-17, CTACK, TNFα, IL-2Rα, IL-8, and SCGFβ were different in Complete Responders (CR) and Nonresponders (NR) groups. At T0 and T1, the SCGFβ level was significantly the highest in NR (23.8 and 40.7 ng/mL, respectively), followed by early recurrence (25.4 and 25.0 ng/mL), and CR (6.7 and 5.3 ng/mL), independently from HCV, stages, and treatment type. Low basal SCGFβ level was associated with longer disease-free survival compared to high SCGFβ. CONCLUSION: In this study, for the first time, we demonstrate that the high level of serum SCGFβ at pre- and posttreatment is associated with HCC nonresponsiveness.